Andrew Shorten’s Multiculturalism: The Political Theory of Diversity Today - Hasene Durgut (Central European Journal of Educational Research)
Bibliography of the reviewed book: Shorten, A. (2022). Multiculturalism: The political theory of diversity today. Polity Press.